PENERAPAN APLIKASI ANDROID “OJEK GT” SEBAGAI STARTUP INDUSTRI KREATIF MENUJU SOCIETY 5.0 - Riovan Styx Roring (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Implementation of technology that supports Society 5.0 needs to be done because the principal itself that focused towards technology implementation and not inclined emphasize to the technology development. Furthermore, 5.0 era also priotize technology implementation to all element of the society that could be used by diverse aspect in the community, such as: economics, education. Infrastructure, and community expertises. One of the support technology utilization is Costless Transportation Application Ojek GT base don Android Client and PHP: Hypertext Preporcessor (PHP) Web as server. This application designed using both of the platform above to fulfill the user’s need. Both of the platform are integrated using Application Programming Interface (API) as a data exchange medium to the database. The implementation of the software itself follows the Community Service Freedom Technology (CSFT) that designed as software development pattern which aims to push support technology utilization towards Society 5.0 era. In the future, this software is expected to be a simple of support technology utilization in Society 5.0 era that could be implemented to all the aspect in the community cope. Beside as a solution of costless technology utilization, Ojek GT could also be expected as Business Startup in the creative industry scope.